2019
DOI: 10.1177/1847980419862075
|View full text |Cite
|
Sign up to set email alerts
|

Captive-air-bubble aerophobicity measurements of antibiofouling coatings for underwater MEMS devices

Abstract: In this article, we report the measurement of underwater aerophobicity, through the captive-bubble method, for different polymeric coatings employed to protect microscale and nanoscale flexible electronic devices for seawater applications. Controlling the morphology and wettability of the coating, in particular with the incorporation of nanoparticles of fluorinated polymers, allows to adjust the hydrophilic/hydrophobic (aerophobic/aerophilic) character of the surface in order to achieve a more insulating and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…This approach can be used as a preliminary step before being subjected to advanced reported techniques to improve removal efficiency. Several authors reported on a new methodology to remove pharmaceutical contaminants from wastewater, such as (a) triboelectric generator, (b) microalgae, (c) nanofiltration membrane bioreactor, (d) polymeric coating, and (e) piezoelectric electrospun nanofiber membrane [ 19 , 20 , 21 , 22 , 23 ]. Khushwaha et al developed a triboelectric generator as an efficient and green approach (80% degradation efficiency achieved using the triboelectric effect) to treat wastewater [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can be used as a preliminary step before being subjected to advanced reported techniques to improve removal efficiency. Several authors reported on a new methodology to remove pharmaceutical contaminants from wastewater, such as (a) triboelectric generator, (b) microalgae, (c) nanofiltration membrane bioreactor, (d) polymeric coating, and (e) piezoelectric electrospun nanofiber membrane [ 19 , 20 , 21 , 22 , 23 ]. Khushwaha et al developed a triboelectric generator as an efficient and green approach (80% degradation efficiency achieved using the triboelectric effect) to treat wastewater [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The working principle of these methods are based on the generation of free radicals (hydroxyl group) using a powerful oxidizing agent [18]. Several new approaches have been reported to remove pharmaceutical contaminants from wastewater, such as a triboelectric generator, microalgae, nanofiltration, membrane bioreactor, polymeric coating, and piezoelectric electrospun nanofiber membrane [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The methods for preparing the coatings are also reported in [52]. Moreover, in this work, the temperature was kept inside the range allowed by the device materials.…”
Section: Methodsmentioning
confidence: 99%
“…The whole devices and some coated silicon substrates (three for each coating) were submerged in a tank (440 × 265 × 240 mm 3 ) and filled with seawater which was aimed at reproducing the marine environment (Figure 5a). The natural seawater was collected from the Ionian Sea, with the following physico-chemical parameters: salinity 3.5%, pH 8, metals (Na 10,784 ppm, K 399 ppm, Mg 1294 ppm, Ca 4120 ppm, Si 2.9 ppm), halogenides (Br − /Cl − /F − 19360/67.5/1.3 ppm), carbonates (HCO 3 − 126 ppm), sulphates (SO 4 2712 ppm), and dissolved gases (O 2 7 ppm, N 2 12.5 ppm) [52].…”
Section: Methodsmentioning
confidence: 99%
“…(E) Proposed working principle for the TENG under finger tapping: the steps of the press-release cycle are illustrated and indicated for the inset of the output voltage signal.The TENG proposed in the present work is envisioned to be easily employed in distributed arrays to meet the power requirements of various wearable, flexible energy harvesting devices. Moreover, the adoption of parylene C as an external encapsulating friction layer makes the device suitable for employment in harsh environments; for instance, for scavenging energy from falling raindrops, since the protective anti-corrosion and anti-biofouling behavior of parylene have been demonstrated in previous works[60,[66][67][68][69].…”
mentioning
confidence: 99%